Cross-cultural perspectives on policy and practice : decolonizing community contexts - Lavia, Jennifer; Moore, Michele (Routledge, 2010)
Presents a space in which struggles for indigenous knowledge within communities are articulated, valued, heard, and responded to. This book acknowledges that the origins and significance of change are frequently found to be unsettling. It explores different understandings of change that forge sustainable, inclusive and just communities.